A model for a laser-induced cavitation bubble. (November 2020) - Zhong, Xiaoxu; Eshraghi, Javad; Vlachos, Pavlos; Dabiri, Sadegh; Ardekani, Arezoo M.
Highlights: A model for a laser-induced cavitation bubble is developed. The predicted bubble radius agrees with the experimental measurements within 10%. Reduction in bubble radius is primarily due to the evaporation and condensation. The amount of air is less than 1% when the bubble reaches maximum. Peak pressure can occur at the second collapse depending on evaporation coefficient. Abstract: The complex mechanism behind the laser-induced cavitation bubble has led to challenges in its modeling. Current models can only predict the radius of the single laser-induced cavitation bubble over one or two growth and collapse cycles. To fill the gap, we propose a new model that takes into account the liquid compressibility, heat transfer, and non-equilibrium evaporation and condensation. Specifically, we use a new approximation of the temperature gradient at the bubble surface. The four unknown physical parameters in the model are found by fitting to the experimentally measured bubble radius. The predicted bubble radius agrees with the experimental measurements within 10% for several cycles of bubble growth and collapse. The calibrated evaporation coefficient is close to 0.04, which agrees with the value reported in the literature. The maximum potential energy of the bubble is found to have a linear relation with the laser energy. The amount of air is found to be less than 1% when the bubble reaches maximum. Our model predicts that the maximum temperature occurs during the first collapse, but the maximum pressure and extension rate can occur at the second collapse depending on the evaporation coefficient. Evaporation and condensation are found to have a significant effect on the dynamic behavior of the bubble. Increasing the amount of non-condensable air in the bubble helps mitigate the collapsing process, and thus, decreases the maximum pressure, temperature, and extension rate.